2016
DOI: 10.1590/1983-80422016243154
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de crianças sobre o termo de assentimento livre e esclarecido

Abstract: The objective of this study is to describe the knowledge of children and adolescents regarding the information disclosed by the terms of assent used in pediatric clinical research, and report the attitudes of the participants. It is an experimental study with a quantitative approach, conducted in cities in the Northeast of Minas Gerais, Brazil, with 142 participants from 7 to 15 years old, chosen for a clinical study of schistosomiasis. These children and adolescents participated in the assent process using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 37 publications
(53 reference statements)
1
0
0
9
Order By: Relevance
“…In a study conducted with children to identify their knowledge about the SA, 47.8% confirmed that someone could influence their decision to participate in the investigation; most cited the mother (69.1%), followed by the father (13.2%), and the others mentioned some other type of person, such as another family member or the health professional. (10) This result is in agreement with what was observed in the present study regarding the age group of 6-12 years. However, for participants aged 13-17 years, at first, the consent of the responsible person did not prove to be decisive for these teenagers' participation in the study.…”
Section: Discussionsupporting
confidence: 94%
“…In a study conducted with children to identify their knowledge about the SA, 47.8% confirmed that someone could influence their decision to participate in the investigation; most cited the mother (69.1%), followed by the father (13.2%), and the others mentioned some other type of person, such as another family member or the health professional. (10) This result is in agreement with what was observed in the present study regarding the age group of 6-12 years. However, for participants aged 13-17 years, at first, the consent of the responsible person did not prove to be decisive for these teenagers' participation in the study.…”
Section: Discussionsupporting
confidence: 94%
“…Se seleccionaron científicos, doce eran estudios cuantitativos [22][23][24][25][26][27][28][29][30][31][32][33] ocho cualitativos [34][35][36][37][38][39][40][41] . Los lugares de origen de los estudios fueron Estados Unidos 26,27,[29][30][31]39 , Brasil 28,34,40 , Tailandia 24 , Jordania 37,38 , Malawi 41 , Europa 22,23,25,32,33,35,36,39 .…”
Section: Resultsunclassified
“…La literatura encontrada no permite determinar claramente a partir de qué edad un niño puede tomar decisiones válidas y consentir sobre su participación en una investigación 34,41 . Sin embargo, los factores que más influye en la competencia de los NNA para consentir sería su desarrollo cognitivo 23,31,34 , madurez 41 , sistemas sociales 34 , normativas legales, aspectos culturales, religiosos y educativos 22,24,37,38 .…”
Section: Edadunclassified
See 1 more Smart Citation
“…Atualmente, tratando-se da participação de crianças em pesquisas pediátricas e biomédicas, têm se levado em consideração o consentimento, envolvimento e disposição das mesmas mediante o processo, para além dos pais. O que evidencia a valorização da criança também como sujeito na pós modernidade, uma vez que ela se apropria de participar das pesquisas, deverá ela também participar como protagonista de seu tratamento (Lobato et al 2016).…”
Section: Introductionunclassified